1978
DOI: 10.1172/jci109041
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Plasma Triiodothyronine and Local Thyroxine Monodeiodination to Triiodothyronine to Nuclear Triiodothyronine Receptor Saturation in Pituitary, Liver, and Kidney of Hypothyroid Rats

Abstract: A B S T R A C T Inijections of triiodothyronine (T3)and thyroxine (T4) into chronically hypothyroid rats were used to evaluate the contribution of intracellular T4 to T3 conversion to nuclear T3 in pituitary, liver, and kidney, and to correlate the occupancy of pituitary nuclear T3 receptors with inhibition of thyroid-stimulating hormone (TSH) release. Injection of a combination of 70 ng T3 and 400 ng T4/100 g body wt resulted in plasma T3 concentrations of 45+7 ng/dl (mean±+-SD) and 3.0±0.4,ug/dl T43 h later.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(86 citation statements)
references
References 44 publications
5
78
0
3
Order By: Relevance
“…Indeed, some studies showed that hypothyroid patients treated with L-T 4 had impaired well-being despite their normal TSH levels (15,16). Meanwhile, patients with moderately suppressed TSH levels postoperatively had higher serum FT 4 levels and unchanged serum FT 3 levels compared with their native levels, findings that are in agreement with those of Silva & Larsen (13). Indeed, most physicians encounter patients on TSH-suppressive doses of L-T 4 therapy who have serum T 4 levels higher than the normal upper limit and normal T 3 levels (2,3,5).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Indeed, some studies showed that hypothyroid patients treated with L-T 4 had impaired well-being despite their normal TSH levels (15,16). Meanwhile, patients with moderately suppressed TSH levels postoperatively had higher serum FT 4 levels and unchanged serum FT 3 levels compared with their native levels, findings that are in agreement with those of Silva & Larsen (13). Indeed, most physicians encounter patients on TSH-suppressive doses of L-T 4 therapy who have serum T 4 levels higher than the normal upper limit and normal T 3 levels (2,3,5).…”
Section: Discussionsupporting
confidence: 76%
“…However, serum TSH levels only reflect the feedback effect of thyroid hormones at the hypothalamic-pituitary level and, therefore, may not be an appropriate indicator of peripheral tissue euthyroidism (12). The TSH secretion from the pituitary is negatively regulated primarily by T 3 produced locally via the conversion of T 4 transported from the peripheral blood, which is keeping with the view that serum T 4 rather than T 3 has a dominant role in regulating TSH secretion (13). On the other hand, T 3 transported from the peripheral blood also has a role in regulating TSH secretion by the pituitary (14).…”
Section: Discussionmentioning
confidence: 96%
“…Estimates suggest that at least half of the T 3 present in D2-expressing tissues is produced locally from deiodination of T 4 (86)(87)(88)(89). More recently D2 expression has been found in a large number of tissues and cells (90)(91)(92)(93)(94)(95)(96)(97)(98), illustrating the importance of defining its contribution to tissue-specific thyroid hormone signaling.…”
Section: [B3] Sources Of Tissue T 3 and Tr Saturationmentioning
confidence: 99%
“…Studies have been standardized in rats but could in theory be applied in mice as well, provided that limitations due to body size and anesthesia are overcome. Tissues can be studied as a whole or fractionated to isolate the TR-containing nuclear fraction (66,(86)(87)(88)(89) 3 . Because the Tm(T 4 ) and Tm(T 3 ) are different, the administration of the two tracers should be timed so that both Tms coincide at the time animals are killed.…”
Section: [B3] Sources Of Tissue T 3 and Tr Saturationmentioning
confidence: 99%
“…Approximately 50 to 60 % of T3 bound to TRs is locally produced by D2-mediated T4 to T3 conversion in the rat pituitary gland (Silva & Larsen, 1978). Human pituitary tissues also contain D2 (Itagaki et al, 1990).…”
Section: Triiodothyronine Is a Negative Regulator Of Thyroid-stimulatmentioning
confidence: 99%